The Effect of Air Pollutants on liver Enzymes and Pituitary Gland Hormones of Smokers and non-smokers of Oil Refinery and Gas Station Workers in Basra/Iraq - Rafad A. Al-Hulfi; Bushra Abdul Mohsin Al Salem; Ibrahim M. Al-Naiema (Institute of Medico-legal Publications Pvt Ltd, 2022)
Air pollutants that originated from oil refineries and gas pump stations can have a negative effect on humanorgans, especially liver and brain. This study focuses on evaluating the pollutants from oil refinery and gasstation on workers’ health by measuring three hepatic enzymes GOT (Glutamic Oxaloacetic Transaminase),GPT (Glutamic Pyruvic Transaminase), ALP(Alkaline phosphatase) and three pituitary gland hormones LH(Luteinizing hormone), FSH (Follicle-stimulating hormone), TSH (Thyroid-stimulating hormone). Study groupswere (i) 33 males from Basra oil refinery workers including 16 smoker and 17 non-smoker (ii) 23 male from Gasstation, 11 of them were smoker while the other 12 are non-smoker (iii) 24 male local volunteers from Basra (allhad non-oil related job) as a control group, 12 smoker and 12 non-smokers. All three groups’ subjects had neitherfamily history of raspatory problems nor diabatic. The results indicated a significance decrease in FSH, LH, TSHhormones and GPT, ALP enzymes of oil refinery workers, comparing to the control group. The same trend wasalso observed among gas station workers, suggesting hepatotoxicity and alternation in pituitary hormones.Pollutants that circulating around oil industry sites can negatively impact human body especially for those whowork near these locations.